Análise do uso de jogos didáticos de biologia no ensino médio : desvelando sua eficácia na aprendizagem dos alunos - Santo, Pâmala Jéssica de Oliveira (2014)
This research investigated the effectiveness of educational game on student learning in high school biology process. The didactic game was chosen for this research as a suggestion of the National Curriculum Guidelines for Secondary Education (2002) and have that reinforced by the National Curriculum Guidelines for Secondary Education (2006) indicated. Therefore, the theoretical framework consists of a brief history of science teaching in Brazil, with emphasis on the use of educational resources throughout the twentieth century and also the proposals present in the Brazilian official curriculum documents on the use of the process teaching and learning. For both, were used as support mainly studies Nardi (2005), Krasilchik (2000), Barra and Lorenz (1986), Santos and Mortimer (2006), and the official curriculum documents Brazilians as the National Curriculum Guidelines (1998) and the National Curricular Parameters for the Middle (2002) education. Discussions on the didactic game, its qualities and advantages were based mainly on studies of Huizinga (2000), Kishimoto (1994), Kishimoto (2008), Zanon, Guerreiro e Oliveira (2008), Miranda (2001) and other authors who did research on this feature. The field research was developed in a state school in Aracaju. Classes were given in two classes in the 1st and 3rd year high school using two different instructional procedures. In a class of each level (ie, one 1st and one 3rd year) were given two hours lecture week in a four-week period, using a didactic game - these classes were called "experimental groups". In the other two classes were taught lessons without the use of educational games - these classes are called "control group". Students were assessed through tests and it was found from the analysis of the results that the methodology was effective in games provide more learning contents. Students who used the didactic game had superior performance to students who did not have access to this feature. We sought to understand the students opinions about lessons with educational games and the results showed that students in the experimental classes considered efficient games to promote interaction, cooperation, socialization, motivation, mobilization, interest, encouragement, and dynamic learning contents studied . The students of the control groups expressed that they feel the need to have lessons with games and establish positive relationship with the resource, they demonstrate knowledge of the benefits of this feature. Therefore, the educational games are considered effective remedies with regard to learning and are well accepted by students